2011
DOI: 10.1111/j.1469-7580.2011.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional adaptations in the forelimb muscles of non‐human great apes

Abstract: The maximum capability of a muscle can be estimated from simple measurements of muscle architecture such as muscle belly mass, fascicle length and physiological cross-sectional area. While the hindlimb anatomy of the non-human apes has been studied in some detail, a comparative study of the forelimb architecture across a number of species has never been undertaken. Here we present data from chimpanzees, bonobos, gorillas and an orangutan to ascertain if, and where, there are functional differences relating to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 72 publications
3
54
1
Order By: Relevance
“…Lower stride frequencies are consistent with the finding of Myatt et al. (, ) that no consistent quantitative differences exist in either hindlimb or forelimb muscle architecture between the orang‐utans and the nonhuman African apes, which would imply that longer stride lengths in vertical climbing must be offset by lower stride frequencies. Myatt et al.…”
Section: The Development Of Ideas On Hominizationsupporting
confidence: 88%
See 1 more Smart Citation
“…Lower stride frequencies are consistent with the finding of Myatt et al. (, ) that no consistent quantitative differences exist in either hindlimb or forelimb muscle architecture between the orang‐utans and the nonhuman African apes, which would imply that longer stride lengths in vertical climbing must be offset by lower stride frequencies. Myatt et al.…”
Section: The Development Of Ideas On Hominizationsupporting
confidence: 88%
“…Although Myatt et al. () found no differences in hindlimb muscle architecture in a larger sample of species and individuals, available evidence still suggests that muscle moment arms of orang‐utans and gorillas differ (Payne et al. ) and, kinematically, gorillas appear to have a smaller abduction of the hip, but greater flexion of the swing‐leg, whereas orang‐utans keep an extended posture of the knee and have higher hip extension (see e.g.…”
Section: The Development Of Ideas On Hominizationmentioning
confidence: 99%
“…Arboreal mammals tend to have relatively more muscle mass devoted to the forearms and shanks, and less to the epaxial musculature (Grand, 1983). Myatt et al (2012) reported that the digital flexors of chimpanzees, bonobos, gorillas, and orangutans had the largest PCSAs of all of the distal forelimb muscles. For those that tend to cling and climb, however, the flexors might play a relatively more important role for counteracting the force of gravity.…”
Section: (1) Anatomical Underpinnings To Tetrapod Graspingmentioning
confidence: 99%
“…Schieber (1995) noted that, among mammals, the ability to individuate finger movement increases from ancestral to derived taxa, and is reflected to some extent in species-level differences in muscle structure. For instance, in macaques digits I, II, and V are controlled by relatively fewer multi-tendoned muscles, whereas in humans (and gibbons; Myatt et al, 2012;Diogo, Richmond & Wood, 2012) they tend to be operated by separate mono-tendoned muscles (partly a result of a separate m. flexor pollicis longus belly), resulting in a greater degree of digital independence (Schieber, 1995). In certain frog genera, the forearm muscles are highly differentiated and appear to control each digit individually (e.g.…”
Section: (1) Anatomical Underpinnings To Tetrapod Graspingmentioning
confidence: 99%
“…Physiological cross‐sectional area (PCSA) is calculated from muscle mass ( m m ) and muscle architecture data; fiber length (FL) and pennation angle (the angle between the line of action of the muscle and the fibers), and is considered a better representation of muscle force production than muscle mass alone (Moore et al, ). As PCSA is a representation of maximum isometric force production for individual muscles, the PCSA values of muscles in a limb can be used to interpret biological functions in correlation with skeletal morphology (Myatt et al, ; Thorpe, Crompton, GÜnther, Ker, & McNeill, ). Scratch‐digging mammals have relatively large PCSA values for muscles used as main movers in the power stroke, such as the triceps brachii long head, which reflect a greater number of fibers per unit volume of muscles; this allows them to produce a greater force for scratch‐digging (Moore et al, ; Olson et al, ; Rose et al, ; Rupert et al, ).…”
Section: Introductionmentioning
confidence: 99%